Metal‐Free Meerwein Carboarylation of Alkenes with Anilines: A Straightforward Approach to 3‐Benzyl‐3‐alkyloxindoles. Issue 17 (28th April 2014) - Tang, Shi; Zhou, Dong; Wang, Ying‐Chun
Abstract: A metal‐free, straightforward carboarylation reaction of alkenes with anilines was developed that proceeds through a radical C–H cyclization. In the presence of benzoyl peroxide (5 mol‐%), tert ‐butyl nitrite, and an array of anilines, a wide variety of N ‐arylacrylamides underwent a tandem Meerwein arylation/C–H cyclization to construct the pharmaceutically important 3‐benzyl‐3‐alkyloxindole scaffold in moderate to good yields. Abstract : A metal‐free, straightforward carboarylation reaction of alkenes with anilines was developed. In the presence of benzoyl peroxide, tert ‐butyl nitrite, and an array of anilines, a wide variety of N ‐arylacrylamides underwent a tandem Meerwein arylation/C–H cyclization to construct the pharmaceutically important 3‐benzyl‐3‐alkyloxindole scaffold in moderate to good yields.